2012
DOI: 10.1111/j.1751-7176.2012.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Peripheral Arterial Disease is Associated With Aortic Pressure Augmentation and Subendocardial Viability Ratio

Abstract: Peripheral arterial disease (PAD) is associated with increased cardiovascular mortality that correlates with peripheral perfusion impairment as assessed by the anklebrachial arterial pressure index (ABI). Furthermore, PAD is associated with arterial stiffness and elevated aortic augmentation index (AIx). The purpose of this study was to investigate whether ABI impairment correlates with AIx and subendocardial viability ratio (SEVR), a measure of cardiac perfusion during diastole. AIx and SEVR were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
(68 reference statements)
0
34
0
Order By: Relevance
“…Mosimann et al have shown that SEVR and aortic augmentation index are associated with ankle-brachial arterial pressure in a study of 65 patients with peripheral arterial disease [16]. Prince et al reported significantly lower SEVR in association with ankle-brachial arterial pressure index in 144 patients with type 1 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mosimann et al have shown that SEVR and aortic augmentation index are associated with ankle-brachial arterial pressure in a study of 65 patients with peripheral arterial disease [16]. Prince et al reported significantly lower SEVR in association with ankle-brachial arterial pressure index in 144 patients with type 1 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…A low SEVR has been associated with albuminuria [8-10] and haemoglobin [11], as well as with markers of inflammation in patients with rheumatoid arthritis [12]. Hypertensive patients with reduced coronary flow reserve [13], extreme dippers [14], patients with rheumatoid arthritis [15] or peripheral artery disease [16], women with type 2 diabetes [17] and highly proteinuric CKD patients with an estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m 2 [18] have also been associated with a lower SEVR. Recently, a reduced SEVR was shown to predict cardiovascular mortality in CKD patients [19] and combined endpoint all-cause mortality and end-stage renal disease in patients with type 1 diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an elevation of the AI in subjects with PAD, in other words, an inverse correlation between the ABPI and the AI [8, 9]. A plausible explanation for this finding is that in the arterial tree, pressure wave reflection occurs at the site of increased arterial resistance, and arterial narrowing/severe stenosis is associated with a steep increase in arterial resistance.…”
Section: Discussionmentioning
confidence: 95%
“…Peripheral artery disease (PAD) is one of the manifestations of conditions associated with advanced atherosclerotic vascular damage, but some patients with PAD are asymptomatic. While some markers of vascular damage have been reported to be associated with PAD [8, 9], further study is needed to establish a tool to identify subjects with asymptomatic PAD.…”
Section: Introductionmentioning
confidence: 99%